Within-family intergenerational trends in age at menarche relative to political changes in Czechoslovakia after World War II - Sekajová, Zuzana; Liczbińska, Grażyna; Králík, Miroslav; Čuta, Martin; Ingrová, Pavlína (American journal of human biology, 2022)
OBJECTIVES: The aim of the study was to examine a secular trend in age at menarche (AAM) in the former Czechoslovak (and descendant Slovak and Czech) population in relation to its large-scale political and social events taking place after World War II. METHODS: The study included 211 women aged 18-30 (born during 1984-1998), and their relatives: mothers, sisters, and grandmothers, yielding a total of 421 women. Changes in retrospectively recalled AAM between the three generations of women (oldest-grandmothers, middle-mothers, and youngest-daughters) were studied in pairwise comparisons. Relationships between AAM and the birth/conception date were analyzed relative to three events in the post-WWII Czechoslovakia (1948, 1968, and 1989). RESULTS: AAM was the highest in the oldest generation, slightly lower in the middle generation and the lowest in the youngest generation. Mixed-Effect Model showed statistically significant interaction between the date of conception, historical events, and the period before and after the event. CONCLUSIONS: The recorded decline in AAM is congruent with secular trends reported in the literature. However, the decreasing trend was not linear and included an increase in AAM in women conceived within the five-year period after the invasion of Czechoslovakia by communist armies in 1968.
Keywords: Czechoslovakia; věkové faktory; vývoj mladistvých; 2. světová válka; Retrospective Studies; Československo; Age Factors; ženské pohlaví; menarche; retrospektivní studie; Humans; World War II; Female; Adolescent Development; Adolescent; lidé; mladiství; Menarche